2020
DOI: 10.13189/cea.2020.080503
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Format to Facilitate User Input for the Co-design of a Cardiac Health Unit

Abstract: Experience-based co-design and post occupancy evaluation are two mechanisms adopted for future planning and design of built spaces. They share a common strategy in that they both require input from a prospective, or current, built environment user. In the case of healthcare spaces, these users include doctors, nurses, patients and family. However, obtaining relevant and useful information from these sources is problematic. The users lack any specific conceptual knowledge and skills required in the design proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
(23 reference statements)
0
6
0
8
Order By: Relevance
“…Results of our study also revealed that hospital planners and sociologist should be involved in early stage of design process. A similar position was discussed by Prugsiganont and Jensen [8]; Waroonkun [36] with regard to hospital space management. These studies suggest that Thai hospitals currently experience major problems with space management.…”
Section: Theme 4: Problems and Current Situation Of Hospital Design Policy And Processmentioning
confidence: 66%
See 1 more Smart Citation
“…Results of our study also revealed that hospital planners and sociologist should be involved in early stage of design process. A similar position was discussed by Prugsiganont and Jensen [8]; Waroonkun [36] with regard to hospital space management. These studies suggest that Thai hospitals currently experience major problems with space management.…”
Section: Theme 4: Problems and Current Situation Of Hospital Design Policy And Processmentioning
confidence: 66%
“…However, they commented that Norwegian hospital buildings are obliged to undergo annual evaluation. Healthcare environment research has shown that building evaluations are a prerequisite for successful and continuous quality improvement of the planning and design process and of the healthcare architecture [36]. Our findings also indicated that Thai hospitals are not being evaluated regularly and buildings are outdated which has led to physical environment problems.…”
Section: Theme 3: Hospital Physical Environmentmentioning
confidence: 80%
“…Another term used for participatory or collaborative design is the co-design, which was researched by Caixeta and Fabrício [6] regarding the methods that involve it. Co-design is the project process that searchs to understand and learn from the user his / her expertise regarding the theme addressed in a particular project and context [7,8,9], or still, defined as Experience-based Co-design [10]. Participation in meetings only would not be sufficient to achieve effective user participation, requiring additional techniques for wider user interference.…”
Section: Collaborative Projects With Bandvi: the Methodology Used And Its Resultsmentioning
confidence: 99%
“…Os edifícios hospitalares são considerados organismos complexos, os quais abrigam diferentes funções e atividades, mudanças estruturais, tipos de usuários e fluxos, equipamentos e legislações (DARIVA; MARCONSINI, 2020;SOUZA;BITENCOURT, 2021). A quantidade de variáveis envolvidas e as complexidades inerentes ao projeto criam, muitas vezes, a necessidade da utilização de equipes multidisciplinares de profissionais e gestores na programação arquitetônica destes edifícios, além da participação dos usuários finais (CARVALHO, 2014;MACHRY et al, 2018;WAROONKUN, 2020). Segundo Bullinger et al (2010), apenas o conhecimento dos especialistas não será suficiente para avaliar o projeto devido ao crescimento de sua complexidade, sendo que "a qualidade do edifício será medida do ponto de vista econômico em razão de como ele atende às expectativas dos usuários futuros" (p. 374).…”
Section: Introductionunclassified